Efektivitas Media Poster dan PowerPoint terhadap Pengetahuan Gizi Seimbang pada Anak Migran - Annisa Rahma Fadlillah; Nurhayati Nurhayati; Mulyanti Mulyanti (Universitas Faletehan, 2026)
Many Indonesian children experienced nutritional problems, especially in low-income areas, which risks hindering their growth and development. Many migrant children aged 10-14 years did not know the benefits of balanced nutrition, so the majority still consume foods that are not good for their growth. The purpose of this study was to enhance balanced nutrition knowledge of migrant children. This study was conducted at the Kepong Guidance Center, Malaysia and used quasi-experimental with pre-tests and post-tests. The sample consisted of 30 elementary school students in grades 3–6, divided into two groups: 15 students in poster group and 15 students in PowerPoint group. The data were analyzed using an independent t-test, resulting on p = 0.000 (< 0.05) with a mean difference of 2.133. Students who received nutrition education through PowerPoint media demonstrated a greater improvement in knowledge compared to those who received education through poster media. PowerPoint is more effective than posters in improving students' knowledge of balanced nutrition. Therefore, PowerPoint is recommended as a medium of nutritional education to support the improvement of students' nutritional knowledge and healthy eating behaviors.